PENGEMBANGAN VLOG PEMBELAJARAN MATEMATIKA DENGAN KONTEKS NISAB ZAKAT FITRAH PADA MATERI PERBANDINGAN UNTUK MENINGKATKAN MINAT BELAJAR - Raniati Raniati; Riza Agustiani; Liana Septy (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
This study aims to produce a vlog of learning mathematics in the context of nisab zakat fitrah with a valid category and has a potential effect on students' interest in learning. This research is a design research type of development study with development procedures consisting of a preliminary stage and a prototyping stage with the Tessmer flow, namely formative evaluation (self evaluation, expert review, one-to-one, small group, and field test). The design of the learning vlog uses the context of nisab zakat fitrah. Data collection techniques used are questionnaires and interviews. The research subjects were students of class VIIA of SMP Negeri 2 Plakat Tinggi. The results showed that the learning vlog developed in the valid category and the learning vlog had a potential effect on students' interest in learning based on the results of the N-Gain test of the pretest-posttest questionnaire which got a score of 0.41 and was included in the medium category.